2022
DOI: 10.3389/fmed.2022.877391
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Whole Genome Sequencing of SARS-CoV-2 Circulating During the First Three Waves of the COVID-19 Pandemic in Libreville and the Haut-Ogooué Province in Gabon

Abstract: Since the onset of the COVID-19 pandemic, the SARS-CoV-2 viral dynamics in Africa have been less documented than on other continents. In Gabon, a Central African country, a total number of 37,511 cases of COVID-19 and 281 deaths have been reported as of December 8, 2021. After the first COVID-19 case was reported on March 12, 2020, in the capital Libreville, the country experienced two successive waves. The first one, occurred in March 2020 to August 2020, and the second one in January 2021 to May 2021. The th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The whole genome of 64 Gabonese strains of the beginning of the pandemic provided information on the predominant lineage B.1.1 (51/64) of this period. 23 In conclusion, this study reported the first data on the COVID-19 pandemic in Gabon. The data showed that most of the infected people were asymptomatic.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The whole genome of 64 Gabonese strains of the beginning of the pandemic provided information on the predominant lineage B.1.1 (51/64) of this period. 23 In conclusion, this study reported the first data on the COVID-19 pandemic in Gabon. The data showed that most of the infected people were asymptomatic.…”
Section: Discussionmentioning
confidence: 68%
“… 22 We performed the whole genome of three of the samples from the first cases as part of a study on the genotyping of strains of SARS-CoV-2 circulating in Gabon. 23 These samples 34 (Accesion number GenBank MW512911, GISAID EPI_ISL_8886131), 56 (Accesion number GenBank MW512912, GISAID EPI_ISL_8886132) and 62 (Accesion number GenBank MW512913, GISAID EPI_ISL_8886133) belonged to lineage B.1, A, B.1.356 respectively. The introduction of lineage B was characteristic of the D614G mutation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We proposed several hypotheses that could possibly account for a late emergence and lower spread of COVID-19 in African countries, including the lack of detection and reporting of COVID-19 cases, social distancing, reduced international air traffic flows, climate, the relatively young (asymptomatic cases) and rural population, the genetic polymorphism of ACE2 or other genes involved in the control of viral replication, the use of anti-malarial drugs, and, ultimately, cross-immunity conferred by other viruses circulating in Africa [ 163 ]. Subsequently, our whole genome sequencing analyzes and those of other teams showed that African populations are sensitive to the same lineages as people from other continents [ 164 , 165 , 166 ]. Several studies have shown immune reactivity to SARS-CoV-2 proteins in samples from individuals that were collected before the COVID-19 pandemic, providing definitive evidence that SARS-CoV-2 cross-reactive immune responses may be derived from pre-existing immunity against previous non-SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 93%
“…Diagnosis of COVID-19 relies on detecting SARS-CoV-2 viral RNA from a nasopharyngeal or oropharyngeal specimen [1]. However, the rapid emergence of several variants with higher virulence and infectivity has provoked repeat waves of the deadly pandemic in many countries and raised anxieties about vaccine efficacy and diagnostic accuracy [2]. Rapid classification and tracking of emerging variants are critical for understanding the transmission dynamics of this disease and developing strategies for severing the transmission chain.…”
Section: Introductionmentioning
confidence: 99%